Pengaruh Digital Marketing, Electronic Word of Mouth (e-WOM), dan Kualitas Produk terhadap Keputusan Pembelian Oleh Konsumen Shopee di Kota Batam - Meilin Swastikasari; Winda Evyanto (Lembaga Pengembangan Kinerja Dosen, 2026)
Consumer behavior is changing as a result of the growth of e-commerce, especially when it comes to skincare items sold on marketplaces. Digital marketing tactics and information that circulates online now have an impact on purchasing decisions in addition to product attributes. The purpose of this study is to examine how digital marketing, electronic word-of-mouth (e-WOM), and product quality affect Scarlett customers' decisions to buy on Shopee in Batam City. Customers who have bought Scarlett items through Shopee are given surveys to complete in order to gather data for the quantitative approach. This study used a quantitative survey approach involving 100 respondents who had previously purchased Scarlett products through Shopee in Batam City. The collected data were analyzed using multiple linear regression to examine the partial and simultaneous effects of the proposed variables. The analysis's findings show that digital marketing significantly and favorably influences consumers' decisions to buy. Electronic word-of-mouth also has a favorable and noteworthy impact, suggesting that customer reviews and experiences are crucial information sources in forming consumer confidence and trust. Additionally, although it contributes less than other factors, product quality has been demonstrated to have a favorable and substantial impact on purchase decisions. Concurrently, differences in Scarlett customers' Shopee purchases in Batam City may be explained by digital marketing, e-WOM, and product quality. These results suggest that purchase decisions on marketplace platforms are significantly influenced by efficient digital marketing tactics, competent administration of customer reviews, and reliable product quality.